Corporate Social Responsibility (CSR): A Case Study of Axis Bank Foundation - S, Kavitha (Ushus Journal of Business Management, 2021)
The article aims to study the importance of CSR and the contribution of our industries towards the betterment and well being of the society. Section 135 of the Companies Act, 2013 has been referred to align industrial CSR activities with considered CSR activities from The Government of India. In the recent years, the banking industry has contributed a lot towards CSR. In this article, the author has taken Axis Bank foundation as a sample to study how exactly CSR activities are undertaken in the corporate, the accountability and reporting of CSR, and the utilisation of funds towards the progress of society. To study CSR activities of Axis Bank, CSR reports have been collected for a period of 3 years (2014-2015 to 2016-2017). The complete study is based on secondary data. The analysis shows that Axis Bank is succeeding in allocating the fund, identifying CSR activities and reporting the same through CSR audited report which is handled by the CSR committee.